Stability of biodiesel, its improvement and the effect of antioxidant treated blends on engine performance and emission. Issue 46 (23rd May 2015) - Rashed, M. M.; Kalam, M. A.; Masjuki, H. H.; Rashedul, H. K.; Ashraful, A. M.; Shancita, I.; Ruhul, A. M.
<x xml:space="preserve">Abstract</x> Biodiesel consists of long chain fatty acid esters derived from vegetable oils, animal fats, and used oils.